Diseño de una guía instruccional para el cuidado del recién nacido dirigido a las madres primerizas del Centro de Salud de Latacunga en la provincia de Cotopaxi cantón Latacunga periodo 2014-2015 - Jaramillo Recalde, Jessica Fernanda (2016)
For the accomplishment of this investigative work were used the following methods: Deductive with the accomplishment of didactic activities that are the execution of workshops, trainings, chats, to facilitate the identification of analysis of results of the investigation and as techniques with the survey and interview, counting as the only instrument the questionnaire, which permitted to obtain real information according to the need that the first-time mothers present to acquire major knowledge, in this case delimiting to the women who attend at the Center of Health of Latacunga, Canton, Cotopaxi's province. Though it is true one of the most wonderful experiences that a woman has, to give life, but this transports many other things since they are control and health care the women must have during the stage of gestation to avoid complications in the childbirth, and later the experience of the care to the newborn child. For a first-time mother logically she presents fear and worries that often aren´t absolved neither by their suppliers of health nor for their families. This is the reason because this investigation has developed some of the worries that the first-time mothers have with regard to the care of his firstborn ones, delivering as well as proposed to this problematics an Instructional Guide for the care of the newborn child, directed the first-time mothers.